Peran Layanan Konseling Realitas untuk Membangun Kepercayaan Diri Warga Binaan Mantan Pemakai Narkoba di Lapas Klas II A Curup - Azwar, Beni (IAIN Kudus, 2022)
The Role of Reality Counseling Services to Build Confidence in Inmates of Ex-Drug Users in Class II A Curup Prisons. Indonesia has been declared an emergency drug state, because of its harmful effects, both physically and mentally and social. The year 2021 revealed 19,229 cases with 24,878 people involved. In 2021 Bengkulu with a population of 2,091,314 people, 1055 people are involved in drugs, and for the Curup Class II.A prison, 228 residents are assisted for drug cases, coming from 3 districts (Rejang Lebong, Lebong and Kepahiang). This study is to see the effectiveness of reality counseling in building self-confidence of former drug users. This is very necessary to restore self-confidence, as well as build a positive self-concept during and after being released from prison. Rejection and labeling from the community makes them not confident and sometimes choose to return as users or dealers. This study uses an experimental approach with pre-experiments with 5 drug inmates with varying lengths of detention and remaining prisoners. The research results show that; first, their self-confidence becomes stronger if they are among the inmates, second; worried about the rejection of society that makes it difficult for him to adapt in society. Third; Reality counseling can build self-confidence, by fostering responsibility, truth and the reality of facts, by not condoning his problematic behavior. Fourth; from the counseling assessment they are very satisfied, and forbid drugs.Keywords: Reality Counseling; Self Confidence; Drugs.